Structure-Based Mechanism for Early PLP-Mediated Steps of Rabbit Cytosolic Serine Hydroxymethyltransferase Reaction - Martino L. Di Salvo (BioMed Research International, 2013)
Serine hydroxymethyltransferase catalyzes the reversible interconversion of L-serine and glycine with transfer of one-carbon groups to and from tetrahydrofolate. Active site residue Thr254 is known to be involved in the transaldimination reaction, a crucial step in the catalytic mechanism of all pyridoxal 5′-phosphate- (PLP-) dependent enzymes, which determines binding of substrates and release of products. In order to better understand the role of Thr254, we have expressed, characterized, and determined the crystal structures of rabbit cytosolic serine hydroxymethyltransferase T254A and T254C mutant forms, in the absence and presence of substrates. These mutants accumulate a kinetically stable gem-diamine intermediate, and their crystal structures show differences in the active site with respect to wild type. The kinetic and crystallographic data acquired with mutant enzymes permit us to infer that conversion of gem-diamine to external aldimine is significantly slowed because intermediates are trapped into an anomalous position by a misorientation of the PLP ring, and a new energy barrier hampers the transaldimination reaction. This barrier likely arises from the loss of the stabilizing hydrogen bond between the hydroxymethyl group of Thr254 and the ε-amino group of active site Lys257, which stabilizes the external aldimine intermediate in wild type SHMTs.